2022
DOI: 10.53730/ijhs.v6ns2.6434
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Kinesio taping therapy for pain reduction in carpal tunnel syndrome patients

Abstract: Background: Carpal Tunel Syndrome (CTS) is the most common nerve compression. Some cases of CTS have symptoms. The most common complaint felt by patients is "Nocturnal Acroparesthesia", which is tingling pain at night. Physiotherapy measures can be taken to relieve CTS complaints, one of which is the use of Kinesiotaping. This study aims to analyze the effect of Kinesiotaping on pain reduction in patients with carpal tunnel syndrome by summarizing several previous studies with RevMan 5.3. Subject and Method: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Gräf et al (2022) conducted a systematic review and found positive effects in terms of functionality and pain reduction when kinesio taping was used in combination with other therapeutic tools (Gräf et al, 2022). Moreover, another meta-analysis on kinesio taping (Pramana et al, 2022) also found an improvement in pain reduction.…”
Section: Effect On Neurophysiological Outcomesmentioning
confidence: 99%
“…Gräf et al (2022) conducted a systematic review and found positive effects in terms of functionality and pain reduction when kinesio taping was used in combination with other therapeutic tools (Gräf et al, 2022). Moreover, another meta-analysis on kinesio taping (Pramana et al, 2022) also found an improvement in pain reduction.…”
Section: Effect On Neurophysiological Outcomesmentioning
confidence: 99%